2016
DOI: 10.1002/mds.26797
|View full text |Cite
|
Sign up to set email alerts
|

Endolysosomal dysfunction in Parkinson's disease: Recent developments and future challenges

Abstract: Increasingly, genetic, cell biological, and in vivo work emphasizes the role of the endolysosomal system dysfunction in Parkinson’s disease (PD) pathogenesis. Yet, many questions remain as to the mechanisms by which primary endolysosomal dysfunction causes PD as well as how the endolysosomal system interacts with α-synuclein-mediated neurotoxicity. We recently described a new mouse model of parkinsonism in which loss of the endolysosomal protein Atp13a2 causes behavioral, neuropathological, and biochemical cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 111 publications
1
27
0
Order By: Relevance
“…1). This complexity comes at a price: burdensome demands on the E-L system, which have been increasingly implicated in neurological diseases including PD (Kett and Dauer 2016;Wang et al 2018).…”
Section: Endolysosomal System In Neurons: Custom-made For Neuronal Fumentioning
confidence: 99%
“…1). This complexity comes at a price: burdensome demands on the E-L system, which have been increasingly implicated in neurological diseases including PD (Kett and Dauer 2016;Wang et al 2018).…”
Section: Endolysosomal System In Neurons: Custom-made For Neuronal Fumentioning
confidence: 99%
“…Studies suggest that endolysomal protein ATPase13A2 is involved in mitochondrial homeostasis, protein degradation pathways, and oxidative stress, potentially through the regulation of mono- and divalent cations, such as Zn2+ and H+ (Kett and Dauer, 2016). …”
Section: Atp13a2mentioning
confidence: 99%
“…Although the role of ATP13A2 has not been extensively characterized, studies have demonstrated that ATP13A2 colocalizes with structural lysosomal protein LAMP1/2a and lysotracker in homeostatic conditions, suggesting a role in lysosomal maintenance (Gusdon et al, 2012). A recent study found that ATP13A2 colocalizes with LC3, an autophagosome and late endosomal marker, perhaps specific to the multivesicular body (MVB) (Kett and Dauer, 2016). This suggests that ATP13A2 may be important in fusion of the autophagosome or vesicles from the MVB with the lysosome.…”
Section: Common Pathways In Pd Pathogenesismentioning
confidence: 99%
“…Indeed, proteasome and lysosome inhibitors can delay Tau turnover and promote Tau-driven neuropathology (Zhang et al, 2005;Hamano et al, 2008). However, dysfunction of a third degradative pathway, the endolysosomal system, is also linked to AD and other neurodegenerative conditions that exhibit Tau accumulation, including Parkinson's disease (Rivero-Rios et al, 2015;Kett & Dauer, 2016;Small et al, 2017). Nevertheless, the role of the endolysosomal pathway in the clearance of Tau is almost completely unexplored.…”
Section: Introductionmentioning
confidence: 99%